(untitled) (Quaderni di Gargnano, 2020)
The paper reconstructs some central moments in the reception of Sannazaro’s poetry between the eighteenth and nineteenth centuries. Tracing his editorial fortune and the presence of his lyrical poems in the anthologies of the early eighteenth century, as well as the judgments expressed in the main literary histories of the time, the essay focuses on the establishment of an interpretation of Sannazaro as the first Petrarchist of the sixteenth century. By analysing some Neapolitan critical essays of the nineteenth century (Colangelo, Settembrini, Torraca), it observes in them the tension between a strong sympathy for the historical figure of the author and an even stronger devaluation of his poetry. Il saggio ricostruisce alcuni momenti centrali nella ricezione della lirica di Sannazaro fra Sette e Ottocento. Ripercorrendo la fortuna editoriale e la presenza delle sue rime nelle antologie di inizio Settecento, nonché i giudizi espressi nelle principali opere di storiografia letteraria, si osserva come si affermi allora l’interpretazione di Sannazaro quale primo rappresentante del petrarchismo cinquecentesco. Analizzando alcuni saggi critici dell’Ottocento napoletano (Colangelo, Settembrini, Torraca), si coglie in essi la difficoltà nel conciliare una forte simpatia verso la figura storica dell’autore e una ancor più forte svalutazione della sua poesia.